2018
DOI: 10.4236/ampc.2018.83009
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Condensation and Superfluidity in TmSe<sub>0.45</sub>Te<sub>0.55</sub>

Abstract: In this publication details of the calculation of heat conductivity and thermal diffusivity, compressibility, sound velocity and exciton-polaron dispersion of TmSe 0.45 Te 0.55 will be shown. The properties of excitons, coupling to phonons, producing thus polarons, but also blocking the phonons as running waves lead to an exciton condensation or exciton liquid. Surprisingly this exciton liquid is contained in a macroscopic crystal, a solid nevertheless, which becomes extremely hard due to the exciton liquid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In that manner, we show in figure 4 the ground-state phase diagrams of the excitonic condensate in the (U, ε f ) plane for different phonon frequencies ω 0 at a given electron-phonon coupling g = 0.6. Due to the choice with ε c = 0, the onsite energy ε f represents the overlap between the f -and the cbands, measuring the possible coupling between the electrons and the holes to form the excitons caused by the external pressure [9,33]. At a given phonon frequency, we always find the excitonic condensation state for small |ε f |.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that manner, we show in figure 4 the ground-state phase diagrams of the excitonic condensate in the (U, ε f ) plane for different phonon frequencies ω 0 at a given electron-phonon coupling g = 0.6. Due to the choice with ε c = 0, the onsite energy ε f represents the overlap between the f -and the cbands, measuring the possible coupling between the electrons and the holes to form the excitons caused by the external pressure [9,33]. At a given phonon frequency, we always find the excitonic condensation state for small |ε f |.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In general, the excitonic condensation state is foremost investigated in purely electronic models, i.e., only the Coulomb interaction between the electron and hole is considered [2][3][4][5][6][7][8]. However, recent several experiments have indicated that the lattice distortions also play important roles to anticipate the excitonic condensation state [9][10][11]. For instance, in the pressure-sensitive mixed valence material TmSe 0.45 Te 0.55 , the excitonic condensation state is found in accompanying with an abrupt change of lattice displacement [12].…”
Section: Introductionmentioning
confidence: 99%
“…The realization in bulk materials has been discussed, for example, in TmSe 0.45 Te 0.55 [2] and 1T -TiSe 2 [3], but the evidence for excitonic condensation in these compounds has been far from convincing. The former is a 4f 13 Mott-like system, not a band semiconductor/semimetal [4], and the latter remains metallic and may suffer from strong screening of electron-hole interactions even below the proposed excitonic transition temperature [5].…”
mentioning
confidence: 99%